Peran dukungan sosial dalam mengurangi dampak negatif media sosial terhadap kesehatan mental remaja - Sulistyowati, Anis Anggun (Maliki Interdisciplinary Journal, 2025)
Social media impacts adolescents both positively and negatively. Negative impacts include anxiety, depression, and decreased self-esteem. This study aims to analyze the role of social support in mitigating the negative impacts of social media on adolescent mental health. Using a literature review method, this article concludes that social support from family, peers, and school environments serves as an effective protective factor in maintaining adolescent mental health in the digital era filled with rapid technological changes. Collaborative efforts and community-based interventions are essential components in sustaining these protective effects. This effort not only helps teenagers manage their use of social media wisely, but also builds the psychological resilience needed to face social pressures and the dynamics of self-development during adolescence.